MAP OF EMOTIONS AND ACHIEVEMENTS: STUDY OF CLINICAL UTILITY - dos Santos, Isabel; Costa, Ana; Mesquita, Edgar Martins (Seven Editora, 2025)
Background: Factors such as fun, freedom, pleasure, satisfaction, self-growth, and happiness are promoters of good mental health. The individual constantly seeks to foster their self-growth and, consequently, promote their happiness. Objectives: This study aimed to explore the clinical utility of a therapeutic tool, dubbed "Map of Emotions and Achievements", developed from scratch by the corresponding author, addressing the concepts of self-growth and happiness, as well as the inherent possibility of the human being to overcome, change and grow. Methods: A sample of 110 individuals, aged between 18 and 74 years (M = 41.33; SD = 15.32), a sociodemographic questionnaire, the instrument "Échelle de Mesure des Manifestations du Bien-Être Psychologique" and a semi-structured interview were applied, with the aim of understanding the clinical usefulness of the Map of Emotions and Achievements. Results: The results clearly demonstrate that the tool is beneficial and clinically effective, since the scores obtained at the second moment of evaluation (after using the tool) were higher than the first moment, regardless of the gender and age of the participant. Discussion: Promising results were found in terms of mental health, which emphasizes the importance of the concepts of self-growth and happiness. The data presented indicate that this technique is efficient in consolidating the therapeutic relationship and self-growth. DOI: https://doi.org/10.56238/sevened2024.037-215